(untitled) (Bangladesh Journal of Psychiatry, 2017)
Psychotherapy for child and adolescent with psychiatric disorder is relatively a newer concept in Bangladesh. This cross sectional study was done to determine the pattern of psychotherapy provided by the psychotherapy department for children and adolescents with psychiatric disorder in National Institute of Mental Health (NIMH) from June 2010 to November 2014. Total 121 samples were taken purposefully from the records of psychotherapy department where data were collected retrospectively using check list. Results showed that among respondents more were boys than girls (64.5% vs. 35.5%) whereas their mean (±SD) age was 12.1 (±3.2) years. Majority (47.9%) of them were within class six to class ten. Most of the respondents (89%) were referred from the outpatient department and 11% were referred by inpatient department. Conduct disorder (27.3%), conversion disorder (13.2%), attention deficit hyperactivity disorder (12.4%) and intellectual developmental disorder (9.1%) were common diagnoses of the respondents. It was found that 74.4% respondents attended up to one to five psychotherapy sessions and cognitive behavior therapy (38%) and behavior therapy (25.6%) were most commonly used psychotherapy. Though 60.3% of the respondents improved to certain extent in psychotherapy sessions, patients dropout rate was found as 55.4%. Bang J Psychiatry Dec 2014; 28(2): 53-57